A Case Study of Iranian EFL Learners’ Intensive Speaking Practice to Express Regrets in English Language - Seyyed Hossein Kashef; Parviz Alavinia; Farhad Khabazian (International Journal of Practical and Pedagogical Issues in English Education)
This study aimed to investigate Iranian EFL learners’ expression of regrets in four main contexts. A qualitative case study design was adopted to address the research question. The participants were 3 male Iranian EFL learners. Sadra and Ata were 19 and Mehrdad was 20. The participants were chosen through purposive sampling and spoke Azeri Turkish as their mother tongue. The contexts used for the purpose of the study were a) classroom, b) shopping mall, c) park and d) coffee shop. The participants were instructed in six EFL classes to obtain an understanding of specific syntactic categories and lexical items related to the expression of regrets by their EFL instructor, the second researcher. High Inference observation (HIO) was used to observe the participants’ speaking competence in expressing their regrets at two phases (the first three months and the last two months). Through initial data coding and comparison of the participants’ use of syntactic and lexical items which were investigated during the two time periods (the first three months and the last two months), it was tangible that the participants failed to express their regrets due to lack of syntactic lexical competence and inadequate practice in their first three months role plays in comparison with their linguistic choices related to expression of regrets during the last two months. The participants’ expression of regrets in the four main contexts pursued for five months up to the time when the researchers reached saturation and were empirically confident about the participants’ improvement in this case study. Scrutiny of the data entries (84 extracted data) revealed that the participants could improve their speaking competence in expressing their regrets in five months.